2015
DOI: 10.1073/pnas.1502902112
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent mismatch between axo-axonic synapses and the axon initial segment controls neuronal output

Abstract: The axon initial segment (AIS) is a structure at the start of the axon with a high density of sodium and potassium channels that defines the site of action potential generation. It has recently been shown that this structure is plastic and can change its position along the axon, as well as its length, in a homeostatic manner. Chronic activitydeprivation paradigms in a chick auditory nucleus lead to a lengthening of the AIS and an increase in neuronal excitability. On the other hand, a long-term increase in act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
109
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(122 citation statements)
references
References 44 publications
8
109
4
1
Order By: Relevance
“…Recent work has explored activity-dependent forms of plasticity at the AIS to establish whether these axoaxonic synapses follow the structural modifications described above. Surprisingly, relocation of the AIS after chronic stimulation did not result in a change in synapse location in either dissociated hippocampal neurons or hippocampal slices 58, 59, resulting in a mismatch between the two. From a functional point of view, modelling results revealed that this arrangement actually helps to reduce neuronal excitability levels.…”
Section: The Aismentioning
confidence: 82%
See 1 more Smart Citation
“…Recent work has explored activity-dependent forms of plasticity at the AIS to establish whether these axoaxonic synapses follow the structural modifications described above. Surprisingly, relocation of the AIS after chronic stimulation did not result in a change in synapse location in either dissociated hippocampal neurons or hippocampal slices 58, 59, resulting in a mismatch between the two. From a functional point of view, modelling results revealed that this arrangement actually helps to reduce neuronal excitability levels.…”
Section: The Aismentioning
confidence: 82%
“…In hippocampal neurons, a different strategy is used. It is now well established that either 2 days of optogenetic photostimulation or high potassium depolarisation leads to a cell-autonomous outward shift of the AIS in excitatory neurons 52, 57, 58, 59, accompanied by a reduction in intrinsic excitability 52, 59. This form of structural plasticity that spatially translocates the AIS to a more distal domain in response to increased activity is dependent on calcium influx through L-type calcium channels and activation of the calcium-sensitive phosphatase calcineurin [57].…”
Section: The Aismentioning
confidence: 99%
“…(B) In hippocampal dentate granule cells, depolarization for 3 h shortens the AIS but simultaneously de-phosphorylates voltage-gated Na + (Nav) channels, which offsets the effects of shortening on excitability (Evans et al, 2015). (C) In hippocampal CA1 pyramidal neurons, depolarization for 2 days moves the AIS distally, but axo-axonic synapses remain at the original location, augmenting the suppressive effects of distal movement on excitability (Wefelmeyer et al, 2015). …”
Section: Biophysical Interaction During Structural Plasticitymentioning
confidence: 99%
“…Although this movement is not accompanied by changes in the ion channel composition at the AIS (Grubb and Burrone, 2010), nor in the location of axo-axonic GABAergic synapses (Figure 1C; Wefelmeyer et al, 2015), it results in a spatial mismatch between the axo-axonic synapses and the AIS, augmenting the suppressive effects of the AIS movement. This augmentation occurs because the remaining synapses increase the shunting conductance between the soma and the AIS and reduce the charges reaching the AIS.…”
Section: Biophysical Interaction During Structural Plasticitymentioning
confidence: 99%
“…Over longer timescales of hours to days, the structural and positional features of the AIS can also undergo modifications in response to sustained perturbations in neuronal activity. These structural forms of AIS plasticity—which can include changes in AIS length, position and/or ion channel distribution in both excitatory and inhibitory neurons (Grubb and Burrone, 2010a; Kuba et al, 2010; Muir and Kittler, 2014; Chand et al, 2015; Evans et al, 2015; Wefelmeyer et al, 2015)—have been shown to be associated with changes in neuronal excitability, and may form part of a repertoire of compensatory mechanisms acting to maintain network activity within set limits.…”
Section: Introductionmentioning
confidence: 99%